PELAKSANAAN PERJANJIAN SEWA-MENYEWA ANTARA CV BERJAYA MALINDO DENGAN PT BINA DUTA LAKSANA DI PEKANBARU - Fadhilah, MHD; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Renting is a common thing done by the community and is one form of interaction that is often carriedout. Not infrequently also in practice there are parties who deliberately avoid the implementation of the leaseagreement even in fact some parties fled in order not to carry out the agreements they had previously made.Looking at the contract agreement with Number 15 / SNBT-BMC / February 2016 / February 15, 2016 betweenPT Bina Duta Laksana Pekanbaru and CV Berjaya Malindo (Pekanbaru Pekanbaru Rent Car) as the owner ofthe vehicle, there has been a default from the provisions of Article 1238 Civil Code (Civil Code). Therefore theformulation of this thesis writing problem is: First, how is the implementation of the lease agreement betweenCV Berjaya Malindo and PT Bina Duta Laksana in Pekanbaru. Second is the effort made by CV BerjayaMalindo in the implementation of the lease agreement with PT Bina Duta Laksana?This type of research can be classified in the type of empirical or sociological legal research, because inthis study the author immediately conducts research on the location or place under study in order to provide acomplete and clear picture of the problem under study. This research was conducted in the City of Pekanbaru,especially in the company CV Berjaya Malindo (Jaya Rent Car Pekanbaru) with the company PT Bina DutaLaksana Pekanbaru. Data sources used, namely: primary data, secondary data and tertiary data. The datacollection technique in this study was by observation, interview and literature review.Conclusions from the results of the study, first, The implementation of a vehicle leasing agreementbetween CV Berjaya Malindo and PT Bina Duta Laksana in Pekanbaru is since the agreement of the rentingparty and the lessee regarding the rental price and the leased goods. And the obligations of the parties includedin the lease agreement, as well as the period of implementation and rental prices are up to the parties'agreement. However, the implementation of the vehicle leasing agreement occurred in a default carried out bythe tenant, PT Bina Duta Laksana. Second, the efforts made by those who rent out, namely CV Berjaya Malindoin the implementation of the vehicle leasing agreement, are to issue a Warning Letter or Submission, conductnegotiation or negotiation efforts and collection efforts. The author's suggestion is that the partiesimplementing the vehicle leasing agreement should know well and correctly what are their rights andobligations, and the leasing party must be more careful in carrying out leasing agreements, especially whenconducting a survey of prospective tenants to do with clear and careful to avoid losses.Keywords: Leasing-Default-Company Leasing Agreement